+0  
 
0
104
3
avatar

f(x)=x·e^-x+3x

 Oct 31, 2019
 #1
avatar+7763 
+1

I haven't been active here for a long time, so I will post an answer :)

\(\begin{array}{rcl} f(x) &=& xe^{-x} + 3x\\ f'(x) &=& x\dfrac{d}{dx} \left(e^{-x}\right)+e^{-x}\dfrac{d}{dx} \left(x\right) + 3\dfrac{d}{dx} x\\ &=& x\left(-e^{-x}\right) + e^{-x} + 3\\ &=& (1 - x)e^{-x} + 3 \end{array}\)

.
 Oct 31, 2019
 #2
avatar+107095 
0

Thanks Max,

It is good to see you again :)

Melody  Nov 1, 2019
 #3
avatar
+1

Thank u sm <3 

Guest Nov 1, 2019

38 Online Users

avatar
avatar